Jenis Keluhan dan Cara Penanganan Keluhan di Hotel Holiday Inn Resort Baruna Bali - Gede Rendrawan Rendrawan; Trianasari Trianasari; A.A. Ngr. Yudha Martin Mahardika (Universitas Pendidikan Ganesha, 2020)
This study aims to determine the types of complaints and how to handle the department f & b service at the Hotel Baruna Bali Holiday Resort. This research is a qualitative descriptive study using interviews and observations as a method of collecting data. The informants who participated in this study were tour operators in the field of administration. The results showed that there were several types of complaints at the F&B Service Department at the Baruna Bali Holiday Resort Hotel. The results showed that the types of complaints by the F&B Service Department at Baruna Bali Holiday Resort Hotel were the lack of professional waiters / waitresses, when serving guests, waiters / waitresses were not polite when serving guests, guests waiting for orders too long. There is a procedure for handling guest complaints at the F&B Service Department at the Baruna Bali Holiday Resort Hotel called ILEAD. This procedure serves as a guideline for employees in the department f & b service in handling complaints